Upaya Peningkatan Pengetahuan Tentang Kebugaran Jasmani dan Kesehatan Mental Di Era Pandemi Covid-19 Melalui Workshop Home-Based Training Program Berbasis Virtual Conference - Rifqi Festiawan; Indra Jati Kusuma; Ngadiman Ngadiman; Neva Widanita (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2021)
The COVID-19 pandemic has had a major impact on physical activity behavior globally. The pandemic has forced many people around the world to stay at home and isolate themselves for a certain period of time, this has a negative impact on health, especially physical fitness and mental health for the community in general and members of the MGMP Sub Rayon I Banyumas Regency in particular. Other problems that arise at this time include 1) Lack of knowledge about the importance of exercising during a pandemic, 2) Lack of understanding of the relationship between exercise, physical fitness, and mental health and 3) Lack of understanding of home-based training programs that can be a solution for sports activities in Indonesia. House. The solution to this problem is to conduct workshops related to sports, physical fitness, and mental health. From the results of data analysis, it is known that the significance value of the pretest and posttest is less than 0.05 (sig = 0.02), in other words, there is a significant effect of the workshop held on the knowledge level of the service participants. This is certainly an illustration that a workshop like this can be done to increase knowledge related to other materials.